Educação ambiental dialógica e descolonialidade com crianças indígenas Tremembé: vinculação afetiva pessoa-ambiente na Escola Maria Venância - Lima, Deyseane Maria Araújo (2014)
The proposal for research pervaded decoloniality, promoting dialogue between indigenous knowledge and scientific knowledge about educational practices with a focus on Environmental Education Dialogic (EED) in Eco-Relational Perspective (ERP), which aims the deconstruction of exclusion and discrimination. The general objective was to analyze the affective link between Tremembé indigenous children and differentiated school environment as descolonialization strategy regarding the fabric of environmental knowledge, based on EED and ERP. The specific objectives were: to investigate the affective link between educators and Tremembé children; analyze the coloniality/environmental decoloniality in the relationship between person-environment; understand the meanings of childhood for Tremembé indigenous people and analyze educational practices of decolonialization based on affective ties between Tremembé children and reality. The methodological trajectory of the thesis focuses on the Qualitative Approach and the Engaged Intervention Research in EED and ERP. We feature authors and actors of research (children, educators, Tremembé leaders) and detail the stages of data collection, such as carrying out semi-structured interviews, workshops, participative observation and documentary research; for data analysis, we used content analysis. In this study, the proposition was to observe and interact with children, considering them subjects who have something meaningful to say to us in relation to educators, families and the community. We investigate the meanings of childhood for Tremembé as a singular being and with particular way of being, because it is related to the specificities of culture, social context, life history and family relationships, as we see in other childhoods constitutions, because we consider children, in general, unique. We mainly focused on investigating the affective link between indigenous Tremembé children and differentiated school environment as decolonialization strategy regarding the environmental fabric of knowledge, based on Dialogic Environmental Education in Eco-Relational Perspective, that we consider essential bonding in the relationship between educators and Tremembé children for the establishment of a Differentiated School Education. It was possible to examine the relationship between children and the environment, which have permeated influences of decolonialization, other realities and the presence of educational practices with Tremembé children and educators. It is crucial for indigenous and non-indigenous humans value the indigenous culture (of various ethnicities). It was essential to analyze daily life, the activities, relationships with family and community, the ways to play, how they learn and teach in their culture. The research promoted dialogic and affective relationship between child and environment in an indigenous context Tremembé in an education that recognizes the environmental and emotional issues in training, production, reframing, and knowledge acquisition process. This work has generated contributions for Differentiated School Education to Tremembé Children and their relationships with family and the community, as was a proposal of praxis interaction with reality, ie, the development in partnership of environmental and popular knowledge by social actors /authors and the researcher.